Case Report: Solitary Extramedullary Plasmacytoma in the Cervix Misdiagnosed as Cervical Cancer - Wang, Ji; Jiang, Lin; Ma, Xuejin; Li, Tingchao; Liu, Heng; Chen, Xiaoxi; Li, Shiguang (Frontiers in Oncology, 2021)
Solitary plasmacytoma (SP) is a malignant tumor caused by the monoclonal proliferation of plasma cells, representing less than 5% of plasma cell tumors. SP can be categorized into two groups: solitary bone plasmacytoma (SBP) and solitary extramedullary plasmacytoma (SEP). SEP most commonly occurs in the head and neck and is rarely located in the reproductive system. Here, we report a case of a 77-year-old woman with SEP in the cervix who had a 7-day history of vaginal bleeding. Ultrasonography and magnetic resonance imaging (MRI) showed an oval mass in the cervix, which was initially considered as cervical cancer. Subsequently, cervical biopsy showed that the tumor was SEP, and then the patient underwent surgery. The postoperative pathological diagnosis was also SEP, which confirmed the radiologist's misdiagnosis. In conclusion, SEP that occurs in the cervix is remarkably rare, and only nine cases have been reported in the cervix. This study demonstrates the MRI imaging information of a patient with SEP of the cervix and reviews the imaging findings of SEP reported in the previous literature, in order to provide more extensive insights for radiologists to consider the differential diagnosis of cervical lesions.